CD99 and polymeric immunoglobulin receptor peptides deregulation in critical COVID‐19: A potential link to molecular pathophysiology?. Issue 20 (21st August 2021) - Siwy, Justyna; Wendt, Ralph; Albalat, Amaya; He, Tianlin; Mischak, Harald; Mullen, William; Latosinska, Agnieszka; Lübbert, Christoph; Kalbitz, Sven; Mebazaa, Alexandre; Peters, Björn; Stegmayr, Bernd; et al.
Abstract: Identification of significant changes in urinary peptides may enable improved understanding of molecular disease mechanisms. We aimed towards identifying urinary peptides associated with critical course of COVID‐19 to yield hypotheses on molecular pathophysiological mechanisms in disease development. In this multicentre prospective study urine samples of PCR‐confirmed COVID‐19 patients were collected in different centres across Europe. The urinary peptidome of 53 patients at WHO stages 6–8 and 66 at WHO stages 1–3 COVID‐19 disease was analysed using capillary electrophoresis coupled to mass spectrometry. 593 peptides were identified significantly affected by disease severity. These peptides were compared with changes associated with kidney disease or heart failure. Similarities with kidney disease were observed, indicating comparable molecular mechanisms. In contrast, convincing similarity to heart failure could not be detected. The data for the first time showed deregulation of CD99 and polymeric immunoglobulin receptor peptides and of known peptides associated with kidney disease, including collagen and alpha‐1‐antitrypsin. Peptidomic findings were in line with the pathophysiology of COVID‐19. The clinical corollary is that COVID‐19 induces specific inflammation of numerous tissues including endothelial lining. Restoring these changes, especially in CD99, PIGR and alpha‐1‐antitripsin, may represent a valid and effective therapeutic approach in COVID‐19, targeting improvement of endothelial integrity.